Hubungan Status Gizi dengan Kejadian Infeksi Saluran Pernapasan Akut pada Balita di Puskesmas Kecamatan Kebon Jeruk Bulan Agustus 2016 - Pamela Felita; Hendrik Kurniawan; Anna Maria Dewajanti (Jurnal Kedokteran Meditek, 2018)
Acute Respiratory Infection (ARI) is one of the main causes of patients to visit health facilities. The incidence and prevalence of ARI in Indonesia in 2013 is 1.8 and 4.5%, respectively. ARI is still among the top ranks of eleven major causes of morbidity and mortality in children under five in 2013. One of the factors that makes a person get exposed to respiratory diseases is the nutritional status. This study aimed to determine whether there is a relationship between nutritional status and the incidence of ARI in infants at Puskesmas Kecamatan Kebon Jeruk on August 2016. Research subjects were toddlers who sought treatment at MTBS (Manajemen Terpadu Balita Sakit) health center in Puskesmas Kecamatan Kebon Jeruk. Eighty-four subjects participated in this study were selected by a consecutive sampling technique. Nutritional status was categorized based on anthropometric standards by measuring body weight age ratio. Among the subjects, 9 infants (64,3%) had bad nutrition and ISPA, whereas 49 infants (70,0%) had good nutrition and ISPA. Statistical analysis using Fisher test obtained a significance value, with a p-value of 0.754 (p> 0.05). The study concludes that there was no association between nutritional status and the incidence of ARI in infants in Puskesmas Kecamatan Kebon Jeruk in August 2016.Keywords: respiratory infections, nutritional status, toddler, Puskesmas Kecamatan Kebon Jeruk